CENTROID-MOMENT TENSOR SOLUTIONS FOR JULY-SEPTEMBER 1987 - Dziewonski, A; Ekstrom, G; Woodhouse, J; Zwart, G (1988)
Centroid-moment tensor solutions are presented for 186 earthquakes that occurred during the third quarter of 1987. The solutions are obtained using corrections for aspherical Earth structure. © 1988.